Performance Evaluation of STM Using Python - Tabassum, Smt.Meenu (International Journal of Advanced Science and Technology, 2020)
In the programming model, we have a Software transactional memory that is performing the transactions in memory. It is an optimistic approach to transactions. In python, we evaluate the Software transactional memory with the help of the multithreading concept. In previous work, they did in Haskell. In this paper, we show the performance of without threads and threads. Each threads evaluating the time and performing the Bank_Account Transactions. In this paper, we have discussed the Software Transactional Memory and concurrency control. It described the use of each thread. Transactions defined as an atomic unit and isolation of serializability. This paper gives the proposed model and evaluates the performance in software-based Transactional Memory.